2008
DOI: 10.1111/j.1750-3841.2008.00716.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant Metabolites and Nutritional Quality of Vegetables

Abstract: Vegetables are an important part of the human diet and a major source of biologically active substances such as vitamins, dietary fiber, antioxidants, and cholesterol-lowering compounds. Despite a large amount of information on this topic, the nutritional quality of vegetables has not been defined. Historically, the value of many plant nutrients and health-promoting compounds was discovered by trial and error. By the turn of the century, the application of chromatography, mass spectrometry, infrared spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
170
0
7

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(195 citation statements)
references
References 228 publications
2
170
0
7
Order By: Relevance
“…Furthermore, both glucose and fructose are glycoxidating agents and are capable of producing reactive compounds (Semchyshyn et al, 2014). The accumulation and concentration of sugars is dependent on several factors such as genotypes, type of tissues, developmental stages, and growing seasons (Hodges et al, 2006;Hounsome et al, 2008;Lee et al, 1970;Nunes, 2008;VandenLangenberg et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, both glucose and fructose are glycoxidating agents and are capable of producing reactive compounds (Semchyshyn et al, 2014). The accumulation and concentration of sugars is dependent on several factors such as genotypes, type of tissues, developmental stages, and growing seasons (Hodges et al, 2006;Hounsome et al, 2008;Lee et al, 1970;Nunes, 2008;VandenLangenberg et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported the importance of plant foods containing nearly all nutrient compounds, vital for human nutrition as well as a large number of health-promoting chemical substances 1 . For instance, amino acids, vitamins C and B, and some plant secondary metabolites such as flavonoids, phenoloc acids, lignans, carotenoids, tocopherols and tocotrienols are essential for human body.…”
mentioning
confidence: 99%
“…Os ácidos fenólicos, os flavonóides e os taninos são considerados as principais classes destes compostos, além de serem apontados como os fenólicos mais abundantes em cereais e leguminosas (SOLOMONS, 2001;HOUNSOME et al, 2008).…”
Section: Compostos Fenólicosunclassified
“…Os ácidos fenólicos são estruturas envolvidas na formação da lignina, fato que explica sua abundância em sementes e cascas de frutas, bem como em caules e folhas de vegetais (HOUNSOME et al, 2008;SOUSA, 2009). Dentro desta classe estão os ácidos hidroxicinâmicos (X a ) e hidroxibenzóicos (X b ), e ainda alguns aldeídos análogos (X c ), como a vanilina e o siringaldeído.…”
Section: Compostos Fenólicosunclassified
See 1 more Smart Citation